2004
DOI: 10.1364/ao.43.006255
|View full text |Cite
|
Sign up to set email alerts
|

Testing fast aspheric convex surfaces with a linear array of sources

Abstract: We describe a noncontact test procedure with which to obtain the shapes of fast convex surfaces. For this, an array of sources is positioned in a straight line and separated in such a way that the image by reflection on the surface consists of a set of equally spaced bright spots. By rotating the surface, we test different meridians such that, after 360 degrees, the entire surface is measured. We present the source array design and the surface evaluation algorithm. We found that, to reduce numerical error in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Papers [2][3][4] describe cases where profile irregularities deteriorate the image in the reflector defective points, which appear as areas of different intensity. Other procedures refer to the analysis of a calibrated mask whose image is reproduced by the concentrator [5][6][7][8]. A method using a colored pattern, projected on a screen through the concentrator, is explained in reference [9].…”
Section: Introductionmentioning
confidence: 99%
“…Papers [2][3][4] describe cases where profile irregularities deteriorate the image in the reflector defective points, which appear as areas of different intensity. Other procedures refer to the analysis of a calibrated mask whose image is reproduced by the concentrator [5][6][7][8]. A method using a colored pattern, projected on a screen through the concentrator, is explained in reference [9].…”
Section: Introductionmentioning
confidence: 99%
“…7, we show spot diagrams for several positions of the images of point objects at the lamps; we obtained the plot assuming that the diaphragm has an aperture with a 10-mm diameter (the aperture of the CCD lens used for the measurement). 3 On the other hand, in the plane of the paraxial image we found that the aberration of coma is predominant, but its magnitude is so small (< 8 µm) that it cannot be resolved by the CCD. In Fig.…”
Section: Aberrations Due To a Steep Surfacementioning
confidence: 70%
“…2 However, it can be difficult to implement these methods for fast aspheres. In a previous work 3 Campos-García et. al.…”
Section: Introductionmentioning
confidence: 94%
“…A positive lens is used to collect and focus these thin pencils of rays onto the CCD sensor. The effects of the aberrations introduced by the positive lens of the camera have been well explained in [18] in which coma and spherical aberrations are considered; the distortion is taken into account by calibrating the camera lens, with a method described below. Departures from a regular array of points on the CCD or image are indicative of deformations of the surface under test.…”
Section: Null-screen Methodsmentioning
confidence: 99%
“…Then the reflected ray, whose direction is given by Eq. (18), intersects the reference surface [Eq. (16)] at P s x s ; y s ; z s (see Fig.…”
Section: Surface Shape Evaluation Methodsmentioning
confidence: 99%